Green Marketing and Digital Marketing Strategies in Increasing Sales Products NTB Waste Bank - Ilhamalimy, Ridho Rafqi; Supratman, Supratman; Septika, Baiq Herdina (BASKARA : Journal of Business and Entrepreneurship, 2023)
Indonesia is one of the countries that still has problems with waste management. Utilization of used goods or non-consumable materials to create environmentally friendly products is the best way to achieve environmental sustainability, including as a solution for waste management in Indonesia. The NTB Waste Bank Shop is one of the a handicraft business that processes waste into an environmentally friendly household product, this study aims to determine what green marketing and digital marketing strategies are being carried out by the NTB waste bank shop in increasing the number of sales of its products. This study used a qualitative method with a purposive sampling technique. Data collection techniques in this research were carried out using observation, interviews and documentation methods. The analytical tool in this research uses the Miles and Huberman model with activity stages in data analysis, namely: data collection, data reduction, data presentation and conclusion drawing/verification. Data collection was obtained from interviews with owners and employees of the NTB waste bank, where the results of the research show that green marketing and digital marketing strategies can increase the number of product sales at the NTB waste bank. So the conclusion of this research is that the NTB waste bank in implementing marketing strategies must continue to be consistent and innovate in order to continue to increase the number of sales, especially digital marketing strategies in the future must be more innovative by adding advertisements that are placed.